Evangelicalism - Bebbington, David (Trajecta, 2017)
This article offers a wide-ranging overview on the rise and identity of the international Evangelical movement, thus offering an over-arching framework for the interpretation of the phenomenon of Evangelicalism in the Low Countries. Evangelicalism began as an eighteenth-century campaign inspired by Wesley and Whitefield in Britain and her colonies for the spread of the gospel. It rapidly became the international enterprise that it was to remain. Its salient characteristics were four: an emphasis on the Bible, a focus on the cross, an insistence on conversion and a summons to activism. The convictions of Evangelicals were originally moulded by the Enlightenment, with its appeal to reason and its endorsement of optimism, science and commerce. Changing cultural currents carried their thinking in fresh directions as the nineteenth century wore on, bringing them to either more liberal or more conservative conclusions. The resulting clash with Modernism created Fundamentalism as an enduring strand of Evangelicalism. Pentecostalism was another major new development of the twentieth century, but there were also others such as the Oxford Group, the East African Revival and the ministry of Billy Graham. The 1960s, though witnessing a decline of churchgoing in the West, also saw the rise of charismatic renewal, the growth of student Christianity and the advance of Calvinistic teaching. The global movement, though diverse, was able to declare its willingness to engage in social change at the Lausanne congress of 1974, but remained committed to undiluted Evangelism.